Hubungan Jumlah Perdarahan Terhadap Kejadian Shivering Pasca Spinal Anestesi di Rumah Sakit Karya Medika I Cikarang Barat - Hasibuan, Verawati; Wibowo, Tophan Heri; Handayani, Rahmaya Nova (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Shivering or the occurrence of teething 1 is one form of response in thermogenesis, which is characterized by an increase in muscular activity that often occurs after anesthesia, especially spinal anesthesia in patients undergoing surgery. Risk factors for shivering after anesthesia include age, duration of surgery, cold environmental temperature and amount of bleeding. The amount of bleeding can affect thermoregulation so that the body compensates for the decrease in body temperature to increase heat production. The purpose of this study was to determine the relationship between the amount of bleeding and the incidence of shivering after spinal anesthesia at Karya Medika I Hospital, West Cikarang. This type of research is a descriptive analytical design study with a cross sectional approach. Sampling using probability sampling technique with saturated sampling (census) of 30 respondents, Research instrument observation sheet The results of the study showed that there was a significant relationship between the amount of bleeding and the incidence of shivering in patients with spinal anesthesia with the results of the Spearman Rank test p value of both variables is 0.001-0.05.